Assessing the impacts of assimilating IASI and MOPITT CO retrievals using CESM‐CAM‐chem and DART. Issue 19 (5th October 2015) - Barré, Jérôme; Gaubert, Benjamin; Arellano, Avelino F. J.; Worden, Helen M.; Edwards, David P.; Deeter, Merritt N.; Anderson, Jeffrey L.; Raeder, Kevin; Collins, Nancy; Tilmes, Simone; Francis, Gene; Clerbaux, Cathy; et al.
Abstract We show the results and evaluation with independent measurements from assimilating both MOPITT (Measurements Of Pollution In The Troposphere) and IASI (Infrared Atmospheric Sounding Interferometer) retrieved profiles into the Community Earth System Model (CESM). We used the Data Assimilation Research Testbed ensemble Kalman filter technique, with the full atmospheric chemistry CESM component Community Atmospheric Model with Chemistry. We first discuss the methodology and evaluation of the current data assimilation system with coupled meteorology and chemistry data assimilation. The different capabilities of MOPITT and IASI retrievals are highlighted, with particular attention to instrument vertical sensitivity and coverage and how these impact the analyses. MOPITT and IASI CO retrievals mostly constrain the CO fields close to the main anthropogenic, biogenic, and biomass burning CO sources. In the case of IASI CO assimilation, we also observe constraints on CO far from the sources. During the simulation time period (June and July 2008), CO assimilation of both instruments strongly improves the atmospheric CO state as compared to independent observations, with the higher spatial coverage of IASI providing better results on the global scale. However, the enhanced sensitivity of multispectral MOPITT observations to near surface CO over the main source regions provides synergistic effects at regional scales.